2008
DOI: 10.1161/strokeaha.107.501932
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Leukoaraiosis and Susceptibility to Infarct Growth in Acute Stroke

Abstract: Background and Purpose-Leukoaraiosis (LA) is associated with structural and functional vascular changes that may compromise tissue perfusion at the microvascular level. We hypothesized that the volume of LA correlated with the proportion of initially ischemic but eventually infarcted tissue in acute human stroke. Methods-We studied 61 consecutive patients with diffusion-weighted imaging-mean transit time mismatch. All patients were scanned twice within 12 hours of symptom onset and between days 4 and 30. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 49 publications
6
124
0
1
Order By: Relevance
“…The image acquisition parameters were summarized in detail elsewhere. 24 For each imaging feature, we calculated interexaminer reliability based on assessment of 200 consecutive patients by 2 examiners blinded to each other's assignments.…”
Section: Methods Patient Population the Primary Derivationmentioning
confidence: 99%
“…The image acquisition parameters were summarized in detail elsewhere. 24 For each imaging feature, we calculated interexaminer reliability based on assessment of 200 consecutive patients by 2 examiners blinded to each other's assignments.…”
Section: Methods Patient Population the Primary Derivationmentioning
confidence: 99%
“…MRI was performed by 1.5 T GE Signa (GE Medical Systems, Milwaukee, WI) or Siemens Sonata (Siemens Medical Solutions, Erlangen, Germany) scanners using the image acquisition and processing protocols that have been summarized in detail previously. 19 Acute ischemic lesion volume on DWI and leukoaraiosis volume on fluidattenuated inversion recovery (FLAIR) images acquired within 24 hours of symptom onset were determined using semiautomated region of interest outlining and volume calculation tools on the MRIcro software (www.mricro.com, University of Nottingham, UK). 9 DWI and leukoaraiosis volume measurements were performed by investigators blinded to the clinical status (TSI or ischemic stroke).…”
Section: Methods Patient Populationmentioning
confidence: 99%
“…21 Indeed, we and others have previously shown that leukoaraiosis severity is associated with a larger ischemic core, mismatch lost, and final infarct volume, supporting this hypothesis. 13,15,22 Indeed, subgroup analyses in patients with available follow-up imaging indicated that worse leukoaraiosis independently predicted larger infarct volumes. However, because infarct volumes could not be measured in all patients, additional studies are required to confirm the association among leukoaraiosis, infarct volume, and outcome.…”
Section: Multivariable Logistic Regression Analysis Of Factors Indepementioning
confidence: 99%